FAKTOR - FAKTOR YANG MENJADI ALASAN WANITA BEKERJA SEBAGAI BURUH DI PERKEBUNAN KELAPA SAWIT (Studi Kasus PT. Brahma Binabakti Kecamatan Sekernan Kabupaten Muaro Jambi) - Agustina, Ester; Sardi, Idris; Putri, Karina Ayu Eka (AGRIPITA JOURNAL, 2018)
The aims of this study are: (1). to know what factors why women works as laborers in oil palm plantations, (2). to know whether or not there are differences in the factors why women work as laborers in oil palm plantations and women who do not work. This research was carried out on February-March 2018. The results of this study indicate that the factors why women work as laborers in oil palm plantations are the level of permanent workers' wages of 95,83% and casual 100%, the income level of the head of the permanent workers 95,83% and casual 58,33%, the number of family dependents of permanent workers was 54,16% and casual 58,33%, the diversity of women's needs of permanent workers was 100% and casual 91.67%, the social status of permanent workers was 100% and casual 91,66%. %, while what is not the reason is that the factor of filling in the permanent labor time of 100% and casual 66.66% and competing and developing themselves are equal to 83,33%. Where as, women do not work the existing factors are not a reason for women to work as laborers where the wage rate is 88,89%, the income level of the head of the family is 88,89%, the number of family dependents is 72,22%, the diversity of women's needs amounting to 88,89%, social status of 88,8%, filling spare time of 100% and competing and developing themselves by 100%.